2009
DOI: 10.5014/ajot.63.5.621
|View full text |Cite
|
Sign up to set email alerts
|

Changing Face of Stroke: Implications for Occupational Therapy Practice

Abstract: Stroke is one of the most life-altering syndromes affecting the world population. Rehabilitation for people experiencing stroke is focused almost exclusively on self-care activities and being able to return home and has little to no focus on work rehabilitation or community reintegration. The Cognitive Rehabilitation Research Group (CRRG) at the Washington University School of Medicine in St. Louis was formed with the vision of improving everyday life for people after stroke by translating knowledge from neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
146
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(147 citation statements)
references
References 20 publications
(22 reference statements)
1
146
0
Order By: Relevance
“…The demographic and medical characteristics of the patients in our sample were compared to those of a large control group (n ¼ 1209) that was selected from the Cognitive Rehabilitation Research Group database 13 of all patients seen at Barnes Jewish Hospital between 2008 and 2013 (n ¼ 6260) using the same inclusion/exclusion criteria. All included stroke and control subjects provided informed consent according to procedures approved by the Institutional Review Board at Washington University.…”
Section: Stroke Source Populationmentioning
confidence: 99%
“…The demographic and medical characteristics of the patients in our sample were compared to those of a large control group (n ¼ 1209) that was selected from the Cognitive Rehabilitation Research Group database 13 of all patients seen at Barnes Jewish Hospital between 2008 and 2013 (n ¼ 6260) using the same inclusion/exclusion criteria. All included stroke and control subjects provided informed consent according to procedures approved by the Institutional Review Board at Washington University.…”
Section: Stroke Source Populationmentioning
confidence: 99%
“…The sample comprised a subset of participants from an existing large stroke cohort (Wolf, Baum, & Connor, 2009). Inclusion criteria were first clinical stroke; no history of schizophrenia or dementia; and availability of required data, which included the acute NIHSS individual item scores, obtained on hospital admission, and the ACS construct scores, collected after the participant had returned home and completed rehabilitation.…”
Section: Participantsmentioning
confidence: 99%
“…The increasing number of working age stroke survivors was also reported in Wolf et al (2009)'s study. They reported that a significant number of people who have had a stroke are less than 55 years old.…”
Section: Introductionmentioning
confidence: 69%